1972
DOI: 10.1111/j.1570-7458.1972.tb02083.x
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS ON THE NUTRITIONAL REQUIREMENTS OF THE SOUTHWESTERN CORN BORER, DIATRAEA GRANDIOSELLA1

Abstract: The southwestern corn borer was reared on a meridic diet containing wheat germ and wheat germ oil as its only plant adjuvants. The insect's requirements for protein, a mineral mixture, and L‐ascorbic acid were studied using a bioassay based on larval growth rate and adult wing condition. The principal results showed that dietary supplements of casein (5.0%), a mineral mixture with nine components (0.9%), and L‐ascorbic acid (0.5%) were essential for optimum growth and development of the insect. RÉSUMÉ OBSERVAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Wing deformity seems to be a problem with southwestern corn borer diet or rearing conditions. Reddy and Chippendale (1972) reported that several nutrient deÞciencies were associated with wing deformities. The insects also may have more problems emerging and expanding the wings in the rearing cups than they would have in tunnels in plants.…”
Section: Discussionmentioning
confidence: 98%
“…Wing deformity seems to be a problem with southwestern corn borer diet or rearing conditions. Reddy and Chippendale (1972) reported that several nutrient deÞciencies were associated with wing deformities. The insects also may have more problems emerging and expanding the wings in the rearing cups than they would have in tunnels in plants.…”
Section: Discussionmentioning
confidence: 98%